Penerapan 5s (Seiri, Seiton, Seiso, Seiketsu, Shitsuke) Dan Program K3 dalam Pemenuhan Standar Fasilitas di Klinik - Egi Mandala Putra (Peneliti.net, 2022)
Iyon Dental Dental Clinic is a business that is engaged in services or services located on Jl. Kalimanggis, Bekasi City. The clinic has one work system, namely by having regular working hours, companies in general or commonly called non-shift and one work system such as MSMEs generally opening services every Monday to Sunday during normal working hours from 08.00 to 20.00 WIB. Based on the results of observations made by researchers at the Iyon Dental Dental Clinic, it was found that the mapping & storage of equipment was not good and could have a significant impact on the process of treatment activities. The tools are stored in one place and combined without cleaning first. The approach that can be taken is to use the 5S concept (Seiri, Seiton, Seiso, Seiketsu, Shitsuke) by solving problems to improve the efficiency of the work environment by removing unnecessary items, cleaning the workplace, and maintaining an efficient work environment